PROCESSING BILIMBI INTO JUMBO RAISIN WITH DIFFERENT SUGAR ADDITIONS - Ema Lestari; Adzani Ghani Ilmannafian; Saripah Saripah (Jurnal Pangan dan Agroindustri, 2021)
Based on its nutritional content, bilimbi contains high vitamin C, high water content, and has a relatively short shelf life. This study aimed to make jumbo raisins to produce raisins preferred by consumers, and analyze its quality based on its water content, vitamin C content, and the level of panelist acceptance. This study used a completely randomized design (CRD) single factor with variations of concentration of sugar solution (50%, 75% and 100%). The quality tests were including water content by drying using an oven, vitamin C content by iodometry, and the level of acceptance through organoleptic tests (taste, color and aroma). The results showed that bilimbi raisin with 100% sugar is preferred by panelists based on its taste (score 3) and aroma (score 3), and had a water content of 11.91% and vitamin C content of 5.13 mg / 100g.